2023
DOI: 10.15447/sfews.2023v20iss4art2
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Transformation and Variation in Invasive Species Abundance Drive Change in Primary Production of Aquatic Vegetation in the Sacramento–San Joaquin Delta

Abstract: Conversion of wetlands in the Sacramento–San Joaquin Delta beginning in the mid-1800s resulted in a pronounced shift from a wetland-dominated food web to one driven by open-water primary producers. Submersed and floating aquatic vegetation (SAV and FAV) now rank highest in potential net primary production (NPP) among producer groups, and provide a comparable amount of carbon to the detrital food web as marshes. However, important details of this contribution that relate to shifts in species composition and hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…The first-order loss formulation in Eqs. 11 and 12 then imply an annual DIN uptake of 34 g N m −2 y −1 , roughly consistent with the carbon uptake estimate of Boyer et al (2023). This rough calculation indicates that uptake by vegetation growth alone could plausibly account for the estimated DIN loss in the model results.…”
Section: Nitrogen Sources Transformation and Sinkssupporting
confidence: 76%
See 2 more Smart Citations
“…The first-order loss formulation in Eqs. 11 and 12 then imply an annual DIN uptake of 34 g N m −2 y −1 , roughly consistent with the carbon uptake estimate of Boyer et al (2023). This rough calculation indicates that uptake by vegetation growth alone could plausibly account for the estimated DIN loss in the model results.…”
Section: Nitrogen Sources Transformation and Sinkssupporting
confidence: 76%
“…While rooted vegetation may take up nutrients from sediment (Novick et al 2015;Boyer and Sutula 2016), Egeria densa, a species of submerged aquatic vegetation that is widely distributed through the Delta (Ta et al 2017;Khanna et al 2022), has been shown to take up most of its nitrogen from the water column (Feijóo 2002). Carbon uptake by Egeria Densa is estimated to be 464 g C m −2 y −1 (Boyer et al 2023). Assuming a carbon to nitrate ratio of 11.1 (Cloern et al 2002), this corresponds to a nitrate uptake of 41.8 g N m −2 y −1 .…”
Section: Nitrogen Sources Transformation and Sinksmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe, prolonged, and frequent drought conditions create cascading ecological effects throughout the Delta that are driven by elevated temperatures, changes to water residence time and primary productivity, and facilitation and establishment of invasive aquatic vegetation that can all detrimentally affect native species (Winder and Jassby 2011;Kimmerer et al 2019;Boyer et al 2023). These effects may affect environmental filtering processes and trophic interactions that limit the distribution and abundance of some species while allowing others to proliferate.…”
Section: Climate Changementioning
confidence: 99%